Clinical Variations of Uveitis in Immuno-Inflammatory Diseases. Review of the Literature. Part 2 - G. A. Davydova; T. A. Lisitsyna; L. A. Kovaleva; E. S. Sorozhkina; A. A. Zaitseva; A. A. Baisangurova (Oftalʹmologiâ, 2023)
In the previous part of the review clinical and diagnostic aspects of some non-infectious uveitis in patients with immunoinflammatory diseases were discussed. In this part we proceed the discussion of ocular manifestations of a number of other immunoinflammatory conditions. In addition to uveitis associated with spondyloarthropathies, rheumatoid arthritis, Still’s disease, juvenile idiopathic arthritis and systemic sarcoidosis described in the previous part, ocular manifestations are also common in systemic vasculitis, systemic lupus erythematosus, Vogt—Koyanagi—Harada syndrome. Despite the numerous diagnostic schemes and therapy algorithms developed to date, much in the pathogenesis of uveitis associated with immuno-inflammatory diseases remains unclear. The need to develop personalized and multidisciplinary approaches for the treatment and diagnosis of non-infectious uveitis in numerous systemic immunoinflammatory diseases remains relevant. In-depth understanding of etiopathogenetic mechanisms of immunoinflammatory processes will allow to develop new approaches in the treatment of patients with uveitis.